Graphene-zinc powder composite material with anti-corrosion effect and preparation method of graphene-zinc powder composite material

By synergistically combining modified graphene with cationic PEG-PLA micelles, the problems of density and compatibility of zinc powder coatings under high humidity conditions were solved, achieving coating densification and improved conductivity, forming a dual anti-corrosion barrier, and significantly extending the anti-corrosion life.

CN121293844APending Publication Date: 2026-01-09HUNAN XINWEILING NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511883508.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing zinc powder coatings suffer from high porosity and insufficient density in marine environments and high humidity conditions, allowing moisture to easily penetrate. Furthermore, the poor interfacial compatibility between graphene and zinc powder leads to coating delamination and agglomeration, failing to meet the requirements for long-term corrosion protection.

Method used

By using silane coupling agent KH-560 to modify graphene and cationic modified PEG-PLA micelles in synergy, the graphene and zinc powder are uniformly composited through micelle encapsulation and cross-linking curing, a dense coating is constructed, which blocks the water penetration path and forms a continuous conductive network.

Benefits of technology

It significantly reduces the water absorption rate of the coating, improves the long-term corrosion resistance, adhesion and conductivity, forms a double anti-corrosion barrier, and extends the anti-corrosion life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293844A_ABST
    Figure CN121293844A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-zinc powder composite material with an anti-corrosion effect and a preparation method of the graphene-zinc powder composite material, and belongs to the technical field of metal powder surface modification. The preparation method comprises the steps of preparation of modified graphene, preparation of cation modified PEG-PLA micelle sol, preparation of composite sol, preparation of graphene-zinc powder composite mixed liquid and forming. The silane coupling agent modified graphene and the cationic micelles are directionally attached and cooperated, so that the interfacial compatibility and the coating compactness are improved, and the problems of agglomeration and pore defects are solved; a dual anti-corrosion system is constructed by means of physical barrier of graphene and sacrificial anode effect of zinc powder, and collaborative optimization of adhesive force, conductivity and low water absorption rate is realized by combining water-borne epoxy resin. The composite material is uniform in dispersion, excellent in coating compactness, low in water absorption rate, capable of effectively blocking moisture permeation and erosion, outstanding in corrosion prevention long-term effect and suitable for metal corrosion prevention requirements of high-humidity, ocean and other humid complex working conditions, and the corrosion prevention technology is promoted to develop towards the low-permeability and high-durability direction.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of metal powder surface modification, and particularly relates to a graphene-zinc powder composite material with a corrosion prevention function and a preparation method thereof. BACKGROUND

[0002] Under complex working conditions such as marine environment, high humidity industrial atmosphere, acid and alkaline humid medium, water penetration is the core inducement of corrosion of metal materials - water not only directly reacts with the metal substrate by electrochemical corrosion, but also carries corrosion media such as chloride ions and hydrogen ions to penetrate the coating, accelerate the corrosion of the substrate, cause the mechanical properties of the material to decay, shorten the service life of the equipment, and even cause safety accidents, so improving the density of the corrosion-resistant coating and reducing the water absorption rate are key technical problems in the field of metal corrosion prevention.

[0003] As a traditional sacrificial anode type corrosion prevention filler, zinc powder provides cathodic protection for the substrate due to its excellent electrochemical activity, but the coating prepared by single zinc powder has defects such as high porosity and insufficient density, and water can easily penetrate into the coating, causing zinc powder to corrode rapidly and fail, and the corrosion prevention life is limited; at the same time, the poor dispersibility of zinc powder and the easy agglomeration of zinc powder further aggravate the porosity defects of the coating, and the conventional way to improve the density depends on increasing the amount of binder, which can seriously damage the conductivity of the coating and weaken the electrochemical protection effect.

[0004] Graphene has a two-dimensional sheet barrier structure and excellent conductivity, and when it is compounded with zinc powder, it can delay water penetration by its physical barrier effect and simultaneously improve the efficiency of electrochemical protection. However, there are still many problems with the graphene-zinc powder composite material: on the one hand, the interface compatibility between graphene and zinc powder is poor, and it is easy to delaminate and agglomerate, resulting in a large number of connected pores in the coating, unobstructed water penetration path, and high water absorption rate; on the other hand, the traditional preparation process cannot achieve uniform distribution of graphene on the surface of zinc powder, the microstructure of the coating is uneven, the density is insufficient, and the simultaneous needs of low water absorption rate, high adhesion and high conductivity cannot be met; in addition, the curing system of some composite materials has poor compatibility with the composite components, and the coating is easy to produce microcracks after curing, further increasing the water absorption rate, and cannot meet the long-term corrosion prevention needs under humid and complex working conditions. Therefore, it is of great significance to develop a graphene-zinc powder composite material that can realize coating densification regulation, significantly reduce water absorption rate, and simultaneously optimize dispersibility, interface bonding force, corrosion resistance and conductivity, and a preparation method thereof, to promote the adaptation of metal corrosion prevention technology to high humidity and harsh working conditions. SUMMARY

[0005] The present application aims to overcome the deficiencies of the prior art and provide a graphene-zinc powder composite material with corrosion resistance and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the present application provides the following technical solutions: A preparation method of a graphene-zinc powder composite material with corrosion resistance, comprising the following steps: S1. Preparation of modified graphene dispersion liquid: graphene powder is added to anhydrous ethanol for ultrasonic dispersion, then silane coupling agent KH-560 is added, and a modified graphene dispersion liquid is obtained after stirring and reaction; S2. Preparation of cationic modified PEG-PLA micelle sol: PEG-PLA block copolymer, DMAEMA and AIBN are added to dichloromethane, and stirring reaction is carried out under nitrogen protection to obtain a cationic modified PEG-PLA micelle sol; S3. Preparation of composite micelle solution: anhydrous ethanol is added to the sol prepared in step S2, dichloromethane is removed by volatilization, then water-based epoxy resin is added, and stirring reaction is carried out under heating, and the composite micelle solution is obtained after natural cooling to room temperature; S4. Preparation of graphene-zinc powder composite mixed solution: zinc powder is added to the composite micelle solution prepared in step S3, stirring is carried out, then the modified graphene dispersion liquid prepared in step S1 is added, and constant temperature stirring is carried out; S5. Composite material forming: the mixed solution prepared in step S4 is coated on the surface of a substrate, and after heating and drying, a corrosion-resistant graphene-zinc powder composite material is obtained.

[0007] The graphene is modified by silane coupling agent KH-560, and a cationic modified PEG-PLA composite micelle system is constructed synchronously, so that the interface compatibility of graphene and zinc powder is improved through the double synergistic effect, the problems of delamination and aggregation are solved, the interstitial gaps between particles are filled, the micro-pores are eliminated, the coating densification is regulated, and the water permeation path is blocked from the structure.

[0008] The bottleneck of the traditional material that the densification is improved while the conductivity and adhesion are unbalanced is broken through, a continuous physical barrier layer is formed by the two-dimensional sheet structure of graphene, the crosslinking and curing effect of the water-based epoxy resin is further improved, the coating densification is further improved, and the water absorption rate is further reduced; meanwhile, the electrochemical conduction efficiency is guaranteed by the graphene bridge conduction effect, the interface bonding force is strengthened by the cationic modified micelles, and the synchronous optimization of low water absorption, high densification, corrosion resistance, conductivity and adhesion is realized.

[0009] The densification regulation principle of the cationic modified PEG-PLA micelles: the copolymerization of PEG-PLA block copolymer and DMAEMA endows the micelles with cationic properties, and the stable micelle space structure formed by the amphiphilic structure can precisely wrap the graphene and zinc powder particles through electrostatic adsorption, limit the particle agglomeration to reduce the generation of pores; on the other hand, the micelle molecular chain can fill the gap between the particles during the solidification process, forming a dense network structure, which significantly reduces the water absorption of the coating.

[0010] The introduction of water-based epoxy resin and composite micelles synergistically, the crosslinking characteristics of epoxy resin can further fill the micro defects of the coating and improve the densification, while not destroying the conductive path of graphene.

[0011] Further preferred is a preparation method of a graphene-zinc powder composite material with anticorrosion effect.

[0012] Preferably, in step S1, the amount of graphene powder is 0.2-0.3g, the amount of anhydrous ethanol is 40-60mL, and the ultrasonic dispersion time is 30-40min.

[0013] Preferably, in step S1, the amount of silane coupling agent KH-560 is 1-2mL, the stirring reaction temperature is 70-90℃, and the reaction time is 3-4h.

[0014] Preferably, in step S2, the amount of polyethylene glycol-poly-lactic acid (PEG-PLA) block copolymer is 1-1.5g, the amount of dimethylaminoethyl methacrylate (DMAEMA) is 0.2-0.4g, the amount of azobisisobutyronitrile (AIBN) is 0.02-0.03g, and the amount of dichloromethane is 20-30mL.

[0015] Preferably, in step S2, the stirring reaction temperature is 70-80℃, and the reaction time is 4-6h.

[0016] Preferably, in step S3, the amount of anhydrous ethanol is 40-60mL, the amount of water-based epoxy resin is 3-5mL, the reaction temperature after heating is 65-75℃, and the reaction time is 1.5-2h.

[0017] Preferably, in step S4, the amount of zinc powder is 2-3g, and the stirring time after adding zinc powder is 30-40min.

[0018] Preferably, in step S4, the constant temperature stirring temperature is 35-45℃, the stirring speed is 350-450r / min, and the stirring time is 1-2h.

[0019] Preferably, in step S5, the heating and drying process is: preheating at 80 DEG C for 20-40 min, and then heating to 110-130 DEG C for 1.5-2.5 h.

[0020] According to the preparation method, the graphene-zinc powder composite material with the corrosion prevention function is obtained.

[0021] Advantages of the present application (1) The synergistic effect of graphene modified by silane coupling agent KH-560 and cationic modified PEG-PLA micelles not only breaks the surface inertness of graphene and improves the interface compatibility, but also realizes the densification regulation of the coating, reduces the particle agglomeration pores through the directional wrapping of micelles, fills the inter-particle gaps through the molecular chains to eliminate micro defects, and significantly reduces the water absorption rate of the coating, thereby blocking the water permeation path from the root.

[0022] (2) The copolymerization of PEG-PLA block copolymer and DMAEMA endows the micelles with cationic properties, and the amphiphilic structure can form a stable micellar spatial structure in the system. On the one hand, the directional wrapping of graphene and zinc powder particles is realized through electrostatic adsorption to limit particle agglomeration; on the other hand, the steric hindrance effect of the micelles can further improve the dispersion of the system, ensuring that graphene is uniformly distributed on the surface and in the gaps of zinc powder, and forming a continuous protective and conductive network.

[0023] (3) The two-dimensional physical barrier effect of graphene and the sacrificial anode effect of zinc powder are synergistic, which builds a double corrosion protection barrier, effectively delays the penetration of corrosion medium, and significantly prolongs the corrosion life; in addition, the cationic modified micelles improve the interfacial adhesion of the material, the waterborne epoxy resin enhances the adhesion of the coating, and the graphene bridge linking conductive effect ensures the electrochemical conduction efficiency, realizing the synchronous optimization of corrosion resistance, conductivity and adhesion. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1 (a) is a scanning electron microscope (SEM) picture of Zn balls, and (b) is a SEM picture of graphene; Figure 2 SEM image of the composite material prepared in Example 1; Figure 3 EIS (electrochemical impedance spectroscopy) image of the composite material prepared in Example 1 and Comparative Example 1; Figure 4 (a)-(c) are coating scratch comparison images of the composite materials prepared in Example 1 and Comparative Examples 1 and 2, respectively; Figure 5 Water absorption rate test result comparison chart of the composite materials prepared in Example 1 and Comparative Examples 1 and 3; Figure 6(a) and (b) are water contact angles of the composite materials prepared in Example 1 and Comparative Example 1, respectively. DETAILED DESCRIPTION

[0025] In order to make the above objectives, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application will be described in detail below with reference to examples. The following content is only an example and description of the concept of the present application. Those skilled in the art can make various modifications or supplements to the described specific implementation cases or use similar ways instead, as long as they do not deviate from the concept of the present application, which shall belong to the protection scope of the present application.

[0026] The above preparation method of the present application will be described below through specific examples and comparative examples.

[0027] Example 1 A preparation method of a graphene-zinc powder composite material with anticorrosion effect, the specific steps are as follows: S1. Preparation of modified graphene dispersion liquid: take 0.25 g of graphene powder, add it into 50 mL of anhydrous ethanol, and place it in an ultrasonic cleaning instrument for ultrasonic dispersion for 35 min. Then add 1.5 mL of silane coupling agent KH-560 into the dispersion liquid, transfer the system to a constant-temperature water bath, and stir at 400 r / min under the condition of 80℃ for 3.5 h. After natural cooling, a modified graphene dispersion liquid is obtained; S2. Preparation of cationic modified PEG-PLA micelle sol: take 1.2 g of PEG-PLA, 0.3 g of DMAEMA, and 0.025 g of AIBN, and add them into 25 mL of dichloromethane. Under nitrogen protection, place it in a 75℃ constant-temperature water bath, and stir at 350 r / min for 5 h to obtain a cationic modified PEG-PLA micelle sol; S3. Preparation of composite micelle solution: add 50 mL of anhydrous ethanol into the cationic modified PEG-PLA micelle sol prepared in step S2, and place it in a fume hood to volatilize and remove dichloromethane at room temperature. Then add 4 mL of water-based epoxy resin, and after the dropwise addition is completed, warm it up to 70℃, and stir at 400 r / min for 1.8 h. After natural cooling to room temperature, a composite micelle solution is obtained; S4. Preparation of graphene-zinc powder composite mixed liquid: add 2.5 g of zinc powder into the composite micelle solution of step S3, and stir at 300 r / min for 35 min. Then add all the modified graphene dispersion liquid prepared in step S1, and stir at 40℃ and 400 r / min for 1.5 h to obtain a graphene-zinc powder composite mixed liquid; S5. Composite material forming: the composite mixture of step S4 is uniformly coated on the surface of Q235 steel substrate (coating thickness is controlled to be 50 μm) by using a coating machine, and then placed in a blast drying oven, preheated at 80 ℃ for 30 min, heated and dried at 120 ℃ for 2 h, and cooled to room temperature to obtain the anti-corrosion graphene-zinc powder composite material.

[0028] Example 2 A preparation method of an anti-corrosion graphene-zinc powder composite material, and the specific steps are as follows: S1. Preparation of modified graphene dispersion liquid: 0.2 g of graphene powder is taken and added into 40 mL of anhydrous ethanol, ultrasonic dispersion is performed for 30 min, 1 mL of silane coupling agent KH-560 is added, stirring reaction is performed at 70 ℃ for 3 h, and a modified graphene dispersion liquid is obtained; S2. Preparation of cationic modified PEG-PLA micelle sol: 1 g of PEG-PLA, 0.2 g of DMAEMA, and 0.02 g of AIBN are taken and added into 20 mL of dichloromethane, stirring reaction is performed at 70 ℃ under nitrogen protection for 4 h, and a cationic modified PEG-PLA micelle sol is obtained; S3. Preparation of composite micelle solution: 40 mL of anhydrous ethanol is added into the sol of step S2, dichloromethane is removed by volatilization, 3 mL of water-based epoxy resin is added, stirring reaction is performed at 65 ℃ for 1.5 h, and the composite micelle solution is obtained after being cooled to room temperature; S4. Preparation of graphene-zinc powder composite mixture: 2 g of zinc powder is added into the composite micelle solution, stirring is performed for 30 min, the modified graphene dispersion liquid of step S1 is added, stirring is performed at 35 ℃ and 350 r / min for 1 h, and the composite mixture is obtained; S5. Composite material forming: the mixture is coated on the surface of Q235 steel substrate (coating thickness is 40 μm), preheated at 80 ℃ for 20 min, heated and dried at 110 ℃ for 1.5 h, and the target composite material is obtained after being cooled.

[0029] Example 3 A preparation method of an anti-corrosion graphene-zinc powder composite material, and the specific steps are as follows: S1. Preparation of modified graphene dispersion liquid: 0.3 g of graphene powder is taken and added into 60 mL of anhydrous ethanol, ultrasonic dispersion is performed for 40 min, 2 mL of silane coupling agent KH-560 is added, stirring reaction is performed at 90 ℃ for 4 h, and a modified graphene dispersion liquid is obtained; S2. Preparation of cationic modified PEG-PLA micelle sol: 1.5 g of PEG-PLA, 0.4 g of DMAEMA, and 0.03 g of AIBN are taken and added into 30 mL of dichloromethane, stirring reaction is performed at 80 ℃ under nitrogen protection for 6 h, and a cationic modified PEG-PLA micelle sol is obtained; S3. Preparation of the composite micelle solution: 60 mL of anhydrous ethanol was added to the sol of step S2, after the removal of dichloromethane by volatilization, 5 mL of aqueous epoxy resin was added, the reaction was stirred at 75°C for 2h, and then cooled to room temperature to obtain the composite micelle solution; S4. Preparation of the graphene-zinc powder composite mixture: 3 g of zinc powder was added to the composite micelle solution, stirred for 40 min, and then the modified graphene dispersion liquid of step S1 was added, stirred at 45°C and 450 r / min for 2h to obtain the composite mixture; S5. Composite material forming: the mixture was coated on the surface of Q235 steel substrate (coating thickness 60 μm), preheated at 80°C for 40 min, and then heated and dried at 130°C for 2.5h to obtain the target composite material after cooling.

[0030] Comparative Example 1 A preparation method of a graphene-zinc powder composite material with anticorrosion effect, the specific steps are as follows: S1. Preparation of modified graphene dispersion liquid: the same as step S1 of Example 1, to obtain the modified graphene dispersion liquid; S2. Preparation of the mixture: 2.5 g of zinc powder was weighed and added to 50 mL of anhydrous ethanol, stirred for 35 min, then the modified graphene dispersion liquid of step S1 was added, and 4 mL of aqueous epoxy resin was added, stirred at 40°C and 400 r / min for 1.5h to obtain the composite mixture; S3. Composite material forming: the same as step S5 of Example 1, the coating and drying to obtain the composite material.

[0031] Comparative Example 2 A preparation method of a graphene-zinc powder composite material with anticorrosion effect, the specific steps are as follows: S1. Preparation of graphene dispersion liquid: 0.25 g of graphene powder was weighed and added to 50 mL of anhydrous ethanol, ultrasonic dispersion for 35 min to directly obtain the unmodified graphene dispersion liquid; S2. Preparation of the cationic modified PEG-PLA micelle sol: the same as step S2 of Example 1; S3. Preparation of the composite micelle solution: the same as step S3 of Example 1; S4. Preparation of the graphene-zinc powder composite mixture: 2.5 g of zinc powder was added to the composite micelle solution of step S3, stirred for 35 min, and then the unmodified graphene dispersion liquid of step S1 was added, stirred at 40°C and 400 r / min for 1.5h to obtain the composite mixture; S5. Composite material forming: the same as step S5 of Example 1, the coating and drying to obtain the composite material.

[0032] Comparative Example 3 A preparation method of a graphene-zinc powder composite material with a corrosion prevention effect, and the specific steps are as follows: S1. 2.5g of zinc powder and 0.25g of graphene powder were weighed and placed in a high-speed mixer, and mechanically stirred and mixed for 30min (rotation speed 1000r / min); S2. 50mL of anhydrous ethanol and 4mL of water-based epoxy resin were added to the mixed powder, and stirred and dispersed for 1.5h to obtain a composite mixed solution; S3. The mixed solution was coated on the surface of a Q235 steel substrate, and the drying process of step S5 of Example 1 was performed to obtain a composite material.

[0033] Figure 1 In (a), the Zn spherical particles have a regular spherical structure, a smooth and dense surface, no obvious pores or defects, uniform particle size, and no agglomeration phenomenon. Figure 1 In (b), the graphene presents a typical two-dimensional sheet structure, the sheet layer is stretched and has a certain wrinkle morphology, which gives the graphene a super-high specific surface area, can fully play its physical barrier and bridging conductive role, and provides structural support for subsequent construction of a continuous corrosion prevention and protection and conductive network.

[0034] In combination Figure 2 (Example 1 SEM image): Figure 2 The composite material particles are uniformly dispersed, the coating is dense, there are no obvious pores or obvious agglomerates, the particle gap distribution is regular, which verifies the directional wrapping and steric hindrance effect of the cation-modified PEG-PLA micelles, and realizes the uniform compounding of graphene and zinc powder.

[0035] Figure 3 The EIS (electrochemical impedance spectroscopy) graph of the composite material prepared in Example 1 and Comparative Example 1 of the application; EIS (electrochemical impedance spectroscopy) is a core means for characterizing the corrosion resistance of a coating, and the higher the impedance value and the larger the impedance arc radius, the stronger the barrier ability of the coating to corrosion medium and the more excellent the corrosion resistance.

[0036] Figure 3 In the above, the impedance arc radius of Example 1 is significantly larger than that of Comparative Example 1 (the corrosion resistance is more excellent), and the impedance value in the low-frequency region is lower than that of Comparative Example 1 (the conductivity is higher): Example 1 constructs a dense coating by modifying graphene and cationic micelles, which not only blocks the penetration of corrosion medium, but also forms a continuous conductive network; Comparative Example 1 has no micelle system, and the particle agglomeration leads to many coating pores and broken conductive paths, which simultaneously weakens the corrosion and conductive properties, and the technical advantages of the application can be verified without additional conductive performance test graphs.

[0037] Figure 4(a)-(c) are scratch comparison diagrams of the coating of the composite material prepared by the present application example 1 and comparative example 1, comparative example 2, respectively; the scratch test of the coating is made by a pencil hardness tester, and the scratch is observed by a microscope, and it can be seen that the scratch of example 1 is obviously shallower than that of comparative example 1 and comparative example 2, which indicates that the adhesion of the sample of example 1 is better, and the core reason is that the coating is dense, has no obvious agglomeration, and has stronger interfacial bonding force.

[0038] Figure 5 Figure 4 is a comparison diagram of water absorption rate test results of the composite material prepared by the present application example 1 and comparative example 1, comparative example 3; the water absorption rate is a core representation of the denseness of the coating, and the lower the value is, the stronger the water blocking ability is. In the figure, the water absorption rate of example 1 (about 0.88%) is significantly lower than that of comparative example 1 (about 3.2%) and comparative example 3 (about 5.5%): example 1 builds a dense structure by the synergistic effect of “modified graphene + cationic micelles”, and blocks the penetration of water; comparative example 1 has no micelles, and comparative example 3 is a traditional mechanical mixing, and both of them have a large number of pores, so water is easy to penetrate, which directly reflects the innovative value of the coating densification regulation of the present application.

[0039] Figure 6 (a) and (b) are water contact angle comparison diagrams of the composite material of example 1 and comparative example 1, respectively, and the greater the contact angle is, the stronger the hydrophobicity of the coating is, the greater the water penetration resistance is, and the better the corrosion resistance is.

[0040] The test shows that the contact angle of example 1 (95.8°) is greater than that of comparative example 1 (84.1°), and the hydrophobicity is better. This is because in example 1, the hydrophobic group is introduced by KH-560 modified graphene, and the cationic PEG-PLA micelles are arranged in a direction to form a hydrophobic interface, so that the surface hydrophobicity is improved by double synergism; in comparative example 1, the composite micelle system is not introduced, the interface compatibility of graphene and zinc powder is poor, the water spreading and penetration resistance is weak, and the hydrophobicity is slightly poor.

Claims

1. A method for preparing a graphene-zinc powder composite having an anticorrosive effect, characterized by, The method comprises the following steps: S1. Preparation of modified graphene dispersion liquid: graphene powder is added into anhydrous ethanol for ultrasonic dispersion, and then silane coupling agent KH-560 is added, and a modified graphene dispersion liquid is obtained after stirring and reaction; S2. Preparation of cationic modified PEG-PLA micelle sol: PEG-PLA block copolymer, DMAEMA and AIBN are added into dichloromethane, and stirring and reaction are carried out under nitrogen protection to obtain a cationic modified PEG-PLA micelle sol; S3. Preparation of composite micelle solution: anhydrous ethanol is added into the sol prepared in step S2, dichloromethane is removed by volatilization, and then water-based epoxy resin is added, stirring and reaction are carried out under heating, and the composite micelle solution is obtained after natural cooling to room temperature; S4. Preparation of graphene-zinc powder composite mixture liquid: zinc powder is added into the composite micelle solution prepared in step S3, stirring is carried out, and then the modified graphene dispersion liquid prepared in step S1 is added, and constant temperature stirring is carried out; S5. Composite material forming: the mixture liquid prepared in step S4 is coated on the surface of a substrate, and the anticorrosive graphene-zinc powder composite material is obtained after heating and drying.

2. The production method according to claim 1, characterized by, In step S1, the amount of graphene powder is 0.2-0.3 g, the amount of anhydrous ethanol is 40-60 mL, and the ultrasonic dispersion time is 30-40 min.

3. The preparation method according to claim 1, characterized in that, In step S1, the amount of silane coupling agent KH-560 is 1-2 mL, the stirring and reaction temperature is 70-90℃, and the reaction time is 3-4 h.

4. The method of claim 1, wherein, In step S2, the amount of PEG-PLA block copolymer is 1-1.5 g, the amount of DMAEMA is 0.2-0.4 g, the amount of AIBN is 0.02-0.03 g, and the amount of dichloromethane is 20-30 mL.

5. The preparation method according to claim 1, characterized in that, In step S2, the stirring and reaction temperature is 70-80℃, and the reaction time is 4-6 h.

6. The method of claim 1, wherein, In step S3, the amount of anhydrous ethanol is 40-60 mL, the amount of water-based epoxy resin is 3-5 mL, the reaction temperature after heating is 65-75℃, and the reaction time is 1.5-2 h.

7. The preparation method according to claim 1, characterized in that, In step S4, the amount of zinc powder is 2-3 g, and the stirring time after adding zinc powder is 30-40 min.

8. The method of claim 1, wherein, In step S4, the constant temperature stirring temperature is 35-45℃, the stirring speed is 350-450 r / min, and the stirring time is 1-2 h.

9. The method of claim 1, wherein, In step S5, the heating and drying process is: preheating at 80℃ for 20-40 min, and then heating to 110-130℃ for drying for 1.5-2.5 h.

10. A graphene-zinc powder composite material with anticorrosive effect, which is prepared by the method of any one of claims 1-9.

Citation Information

Patent Citations

  • Graphene oxide waterborne epoxy coating and preparation method thereof

    CN114133831A

  • Bismuth hydroxide material and preparation method thereof

    CN120440952A